Isolation of Legionella pneumophila by Centrifugation of Shell Vial Cell Cultures from Multiple Liver and Lung Abscesses - La Scola, Bernard (American Society for Microbiology, 1999)
A 7-year-old girl was admitted to the hospital with acute lymphoblastic leukemia and was treated with allogenic cord blood transplantation. At day 30 after graft, she developed a fever and multiple nodular lesions disseminated in the liver and lungs. All bacterial cultures attempted on liver and lung biopsy specimens and blood remained sterile on standard axenic media. However, inoculation of liver and lung biopsy specimens on eukaryotic cell monolayers by the centrifugation-shell vial technique (M. Marrero and D. Raoult, Am. J. Trop. Med. Hyg. 40:197–199, 1989) led to the recovery of a strain of Legionella pneumophila serogroup 1, identified by 16S rRNA gene amplification and sequencing and serotyping. Our findings demonstrate that the centrifugation-cell culture method, which has previously been useful for the isolation of other strictly or facultatively intracellular bacteria, can also serve as a method for the recovery of L. pneumophila from clinical material.